Molecular Detection of TYLCV Isolates from Xinjiang Autonomous Region of China and Analysis of Its DNA-A Genome Sequences - Yingna, Ding; Shifang, Li; Sheng, Zhang; Yuanyu, Cui; Hua, Yang; Wei, He; Xiaojun, Sun (Plant Diseases and Pests(植物病虫害研究：英文版), 2013)
In 2012,the symptoms of dwarf plants,yellowed and curled leaves were observed in tomato,pepper,eggplant,datura,poinsettia,florists cyclamen and anthurium in Kashi,Tulufan and Yili regions of Xinjiang autonomous region in China.The results showed that all of the above seven species of plants could be infected by Tomato yellow leaf curl virus（TYLCV）.We obtained the full-length DNA-A genome sequences of the virus isolate that KSCTo4,KSCTo16, KZPTo18 and KYCTo20 from tomato,KSCPe6 and KSCPe7 from pepper,KSCEg1from eggplant and KSCDa from datura.Each isolate had all of the characteristic features of Begomovirus genome.Virus isolate collected from different hosts had little difference in sequence,and shared the similarity of 99.0%-99.8% with each other.These isolate shared the similarity of 98.6%-99.5% with TYLCV isolate SH3,ZJ6,SD2A-7,HNSQ and HBBD reported in China.